The Influence of Digital Transformation, Inflation, and Economic Growth on Zakat Growth: Evidence from Indonesian - M Bastomi Fahri Zusak (Jeksyah: Islamic Economics Journal, 2026)
This study investigates the complex relationship between digital transformation, inflation, and economic growth in influencing zakat growth in Indonesia. Drawing on panel data from 36 cities over the period 2020 to 2022, the research employs a fixed-effects regression model to examine in detail how varying levels of technological readiness, alongside broader macroeconomic conditions, affect the dynamics of zakat collection and distribution. The empirical findings indicate that, while digital transformation is theoretically expected to expand the zakat collection base, improve efficiency, and strengthen institutional performance, in practice it has thus far exerted a negative influence on zakat growth. This outcome can largely be attributed to the high transition costs associated with the early implementation phase, the uneven distribution of digital literacy, and the relatively low level of public trust in online payment platforms, which collectively limit the effectiveness of zakat mobilization. By incorporating both technological and macroeconomic dimensions into the analysis of zakat, this study not only advances the theoretical discourse within the field of Islamic economics but also provides practical insights and policy recommendations for enhancing the resilience, credibility, and inclusiveness of zakat institutions in the digital era, ultimately contributing to more sustainable and equitable socio-economic development.